Nilai-Nilai Pendidikan Humanis dalam Surat An-Nisa Ayat 63 - Yeti Dwi Herti (Jurnal Kependidikan, 2019)
Abstract Humanist education is one method of learning that emphasizes the human aspects of each student. Through humanist education, each student will be formed into an independent human being. As explained in the Al-Quran, one of which is contained in the An-Nisa verse verse 63. In that verse, it contains the values ​​of humanist education. One of them is humanist-religious education and humanist-liberation education. Through these values ​​will form humans who have superior character, intellectual, physical, and spiritual. Keywords: an-nisa verse 63, humanist education, humanist-religious, humanist-liberation Abstrak Pendidikan humanis merupakan salah satu metode dalam pembelajaran yang menekankan kepada aspek kemanusiaan masing-masing siswa. Melalui pendidikan humanis, setiap siswa akan dibentuk menjadi manusia yang merdeka. Seperti yang telah dijelaskan dalam Al-Quran, salah satunya yang terdapat di dalam surat An-Nisa ayat 63. Di dalam ayat tersebut, mengandung nilai-nilai pendidikan humanis. Salah satunya yaitu pendidikan humanis-religius dan pendidikan humanis-liberasi. Melalui nilai-nilai tersebut akan membentuk manusia yang memiliki keunggulan budi pekerti, intelektual, jasmani, serta rohani. Kata Kunci: an-nisa ayat 63, pendidikan humanis, humanis-religius, humanis-liberasi